Menopausal symptoms and work: A narrative review of women's experiences in casual, informal, or precarious jobs. (August 2021) - Yoeli, Heather; Macnaughton, Jane; McLusky, Sarah
Highlights: The wellbeing of women at menopause is determined less by current working conditions than by early life experiences. Women who were raised amidst socio-economic and educational poverty and other forms of childhood adversity have more difficult menopauses. Whereas women in higher-status work tend to regard vasomotor symptoms as their main physical symptom, women in casual work report musculoskeletal pain as more problematic. Casual work is not inherently detrimental to the wellbeing of menopausal women. Being a casual worker as a woman of typical menopausal age is a strong indicator of the many forms of childhood adversity which lead to difficult menopause experiences. Abstract: Governments, employers, and trade unions are increasingly developing "menopause at work" policies for female staff. Many of the world's most marginalised women work, however, in more informal or insecure jobs, beyond the scope of such employment protections. This narrative review focuses upon the health impact of such casual work upon menopausal women, and specifically upon the menopausal symptoms they experience. Casual work, even in less-then-ideal conditions, is not inherently detrimental to the wellbeing of menopausal women; for many, work helps manage the social and emotional challenges of the menopause transition. Whereas women in higher status work tend to regard vasomotor symptoms as their main physical symptom, women in casual work report musculoskeletal pain as more problematic. Menopausal women in casual work describe high levels of anxiety, though tend to attribute this not to their work as much as their broader life stresses of lifelong poverty and ill-health, increasing caring responsibilities, and the intersectionally gendered ageism of the social gaze. Health and wellbeing at menopause is determined less by current working conditions than by the early life experiences (adverse childhood experiences, poor educational opportunities) predisposing women to poverty and casual work in adulthood. Approaches to supporting menopausal women in casual work must therefore also address the lifelong structural and systemic inequalities such women will have faced. In the era of COVID-19, with its devastating economic, social and health effects upon women and vulnerable groups, menopausal women in casual work are likely to face increased marginalisation and stress. Further research is need.